2006
DOI: 10.1021/tx060164e
|View full text |Cite
|
Sign up to set email alerts
|

Methylating Agents and DNA Repair Responses:  Methylated Bases and Sources of Strand Breaks

Abstract: The chemical methylating agents methylmethane sulfonate (MMS) and N-methyl-N′-nitro-Nnitrosoguanidine (MNNG) have been used for decades as classical DNA damaging agents. These agents have been utilized to uncover and explore pathways of DNA repair, DNA damage response, and mutagenesis. MMS and MNNG modify DNA by adding methyl groups to a number of nucleophilic sites on the DNA bases, although MNNG produces a greater percentage of O-methyl adducts. There has been substantial progress elucidating direct reversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
417
0
12

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(443 citation statements)
references
References 171 publications
14
417
0
12
Order By: Relevance
“…In the "2B/-"model, Pax7 and MyoD expression levels were reduced in SMA myoblasts before differentiation (36). The "2B/-"mice are maintained on a hybrid C57BL/6xCD1 background (83). The CD1 mouse strain is known to differ from other mouse strains on physiological and genetic measures (72)(73)(74)(75).…”
Section: Fayzullina Andmentioning
confidence: 99%
See 2 more Smart Citations
“…In the "2B/-"model, Pax7 and MyoD expression levels were reduced in SMA myoblasts before differentiation (36). The "2B/-"mice are maintained on a hybrid C57BL/6xCD1 background (83). The CD1 mouse strain is known to differ from other mouse strains on physiological and genetic measures (72)(73)(74)(75).…”
Section: Fayzullina Andmentioning
confidence: 99%
“…The mechanism of action of MMS is direct-acting DNA base alkylation (82). The major MMS-induced base lesions are 7-methylguanine and 3-methyladenine (83). The downstream effects of MMS are complex.…”
Section: J Neuropatholmentioning
confidence: 99%
See 1 more Smart Citation
“…MMS introduces BER substrates/intermediates. The most critical biological lesion caused by MMS is presumed to be N-methylation base products, which frequently give rise to AP sites via enhanced hydrolysis of the N-glycosylic bond or DNA glycosylase-mediated base release (Wyatt and Pittman, 2006). CSB deficient cells expressing an ATPase domain II mutant CSB protein (CSBE646Q) display intermediate sensitivity to MMS challenge.…”
Section: Sensitivities Of Csb Deficient Cells To Various Genotoxinsmentioning
confidence: 99%
“…MMS also has a misleading reputation as a radiomimetic capable of directly producing DNAstrand breaks (1). Studies showed that MMS treatment increased intracellular reactive oxygen species (ROS) in Saccharomyces cerevisiae (2,3), and may further depleted glutathione and induced lipid peroxidation and cell death, which processes were reversed by antioxidant activity (4).…”
mentioning
confidence: 99%